SmartHealth: a Service-based Platform for Information Integration and Clinical Evaluation Support - Inês Lopes; Marcos Liberal; Filipe Sousa (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2023)
The stringent regulations related to eHealth products and software design and manufacture can be difficult to overcome. Many businesses can create innovative prototypes, but costs and technical demands for compliance often hinder the process of industrialization and commercialization. SmartHealth is a service-oriented platform for information integration. It aims to support medical device manufacturers in generating new insights from their devices and health apps to assist in the clinical evaluation process while assuring regulatory compliance throughout the entire product development lifecycle. To demonstrate the viability of SmartHealth, the system will be tested against two use case scenarios: an ECG-based device and a Sleep/Room monitoring device. These two products are from two different manufacturers, and the goal is to certify them as medical devices.